Analisis Pengaruh Kualitas Produk dan Citra Merek Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Air Mineral Merek Tirta Tio - Siagian, Ondo Pasuna; Simanjuntak, Mariana (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was aimed to analyze the influence of product quality and brand image on customer loyalty through customer satisfaction of Tirta Tio brand mineral water. This research used quantitative method. The samples were taken from the population using Non-Probability Sampling techniques with Accidental Sampling techniques. The research instrument used to collect data was a Likert scale questionnaire. The instrument was tested using SPSS Amos 26. The data analysis method used in this research was multiple linear regression analysis and hypothesis testing (t test). The research results showed that product quality has a positive and significant effect on customer satisfaction with a high level of influence of 89%, brand image has a positive influence on customer satisfaction with a low level of influence of 9%, product quality has a positive influence on customer loyalty with a medium level of influence of 56% , brand image has a positive effect on customer loyalty with a medium level of influence of 58% and customer satisfaction has a positive effect on customer loyalty with a medium level of influence of 59%. Therefore, it can be concluded that all the variables in this case had an influence even though the level of influence varies.